The Relationship Between Work Discipline and Nurses’ Work Productivity at Hospital X Jakarta - Putri, Gavrila Catherine; Wiharto, Mulyo (Jurnal Multidisiplin Sahombu, 2025)
Work discipline is essential to sustain nursing productivity and hospital performance. This study examines the association between work discipline and nurses’ work productivity in inpatient care at a private hospital in Jakarta. A cross-sectional design was applied with total sampling of staff nurses. Data were collected using validated Likert-type questionnaires for discipline and productivity, then categorized into high and low levels based on central tendency. Bivariate analysis employed an appropriate chi-square procedure and effect size to test the relationship. The findings indicate a meaningful positive association: nurses with higher discipline tend to report higher productivity, reflected in punctual attendance, adherence to standard procedures, and complete documentation of care. The study recommends strengthening managerial supervision, feedback loops, and fair scheduling, alongside continuous education on standard operating procedures. Enhancing discipline culture is expected to raise individual productivity and contribute to better service quality and organizational outcomes in Indonesian hospital settings over time.